Lupus and pregnancy: integrating clues from the bench and bedside - Ruiz-Irastorza, Guillermo; Khamashta, Munther A. (European journal of clinical investigation, 2011)
Eur J Clin Invest 2011; 41 (6): 672–678 Adequate pregnancy care of women with systemic lupus erythematosus (SLE) rests on three pillars: a coordinated medical‐obstetrical care, an agreed and well‐defined management protocol and a good neonatal unit. Pregnancy should be planned following a preconceptional visit for counselling. Women with severe active disease or a high degree of irreversible damage, such as those with symptomatic pulmonary hypertension, heart failure, severe restrictive pulmonary disease or severe chronic renal failure should best avoid pregnancy. Treatment is based on hydroxychloroquine, low‐dose steroids and azathioprine. Patients with antiphospholipid antibodies/syndrome should receive low‐dose aspirin +/− low molecular weight heparin. The addition and the dose of heparin depend on the clinical profile of the patient, i.e. a previous history of miscarriage, foetal loss, placental insufficiency or thrombosis. A close surveillance, with monitoring of blood pressure, proteinuria and placental blood flow by Doppler studies helps the early diagnosis and treatment of complications such as preeclampsia and foetal distress. Postpartum follow‐up is important.